Diseño y gestión del E-commerce para la psicóloga Rachel Watson Delucchi - Ramos Watson, Mariana Rachel (2023)
The present project is about the design and management of e-commerce for the clinical and educational psychologist Rachel Watson Delucchi. This proposal was created during the pandemic caused by COVID-19, with the purpose of providing socio-emotional support to Peruvians who were experiencing difficulties due to the situation. A website was designed and executed in a professional manner to bring a new platform for her services and products, so that her patients and followers can choose the best alternative for their personal, family or business counseling and support.